A key to the known larvae of south american Elmidae (Coleoptera: Byrrhoidea), with a description of the mature larva of Macrelmis saltensis Manzo. - Manzo, María Verónica (2008)
A key to identify the known mature larvae of the South American genera of the family Elmidae is provided. The key includes seven genera presently assigned to the subfamily Larainae and 15 genera assigned to the subfamily Elminae. New distributional data for all genera and a checklist of described larvae are also included. The mature larva of Macrelmis saltensis Manzo is described and illustrated for the first time, and compared to other known larvae of the granigera species-group. Distributional notes for M. saltensis increase its known range to the north, this being the first citation of the species for Bolivia. Macrelmis isis (Hinton) is also cited for the first time for Bolivia.